Per il bene della causa - Solzjenitsyn, Aleksandr (Venezia: Arnaldo Mondadori, 1974)
"Aleksandr Solzenicyn ; traduzioni di Clara Coïsson, Vittorio Strada, Raffaello Uboldi, Pietro Zveteremich Fonds Perrone"